Multi process parameters optimization of Wire-EDM on shape memory alloy (Ni54.1Ti) using Taguchi approach. (2021) - Gupta, Deepak Kumar; Dubey, Avanish Kumar
Abstract: Nickel-based titanium, a shape-memory alloy (SMA), is gaining popularity for use in different applications. Machining of these SMAs shows various challenges through conventional machining. Henceforth, in the current study, the wire-electric discharge process has been attempted to machine nickel-titanium (Ni54.1 Ti) super-elastic SMA. NiTi's effective and net shape machining is critical for the excellent response of this material in medical and other applications. The outcomes in terms of material removal rate (MRR) and surface roughness (SR) were examined by varying input parameters, i.e; pulse on time (Ton ), pulse off time (Toff ) and peak current (Ip ). For planning and designing the Wire-EDM experiments, Taguchi's L27 mixed orthogonal array (L27 OA) was used. After outcomes, it was concluded that Ton was the superlative efficacious parameters for the MRR and SR.